The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0266242617730885
|View full text |Cite
|
Sign up to set email alerts
|

Extending the concept of familiness to relational capability: A Belgian micro-brewery study

Abstract: While research in family businesses has focused on familiness as a resource with potential to generate competitive advantage, a gap exists in understanding how such value can be extended to wider business relationships. We contribute to an increased understanding of how familiness can influence the development of relational capability in entrepreneurial family firms. Using a business relational and family embedded perspective, we advance a conceptualisation of the link between familiness and relational capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 117 publications
(245 reference statements)
0
16
0
Order By: Relevance
“…The more the family identified with the business (i.e., it was once a core business, it had the family’s name on it) the more likely the family would shut it down (in the hope of someday reopening) rather than sell it. Similarly, based on interview data from six Belgian microbrewers, McGrath and O’Toole (2018) found that family firms with strong family identities emphasize relational capabilities within the firm at the cost of external network ties, which results in less collaborative innovation.…”
Section: Research On Business Familiesmentioning
confidence: 99%
“…The more the family identified with the business (i.e., it was once a core business, it had the family’s name on it) the more likely the family would shut it down (in the hope of someday reopening) rather than sell it. Similarly, based on interview data from six Belgian microbrewers, McGrath and O’Toole (2018) found that family firms with strong family identities emphasize relational capabilities within the firm at the cost of external network ties, which results in less collaborative innovation.…”
Section: Research On Business Familiesmentioning
confidence: 99%
“…the unique bundle of resources and capabilities a particular organization possesses because of the family firm system’s interaction among the family, its individual members, and the business” (p. 11). Since that definition was provided, the concept has been widely discussed in the family business field (for a compilation, see Dawson & Mussolino, 2014; Frank, Kessler, Rusch, Suess-Reyes, & Weismeier-Sammer, 2017; McGrath & O’Toole, 2018; Moores, 2009).…”
Section: The Role Of Knowledge For Familiness Sustaining In the Succementioning
confidence: 99%
“…Finally, it has also been underlined that FFs’ managers should extend their social interactions even beyond their FFs to develop trusting relationships with other firms and external stakeholders (bridging social capital) to support the creation of human capital and value across generations (Salvato & Melin, 2008; Sirmon & Hitt, 2003). This relational capability can provide the FF with access to external opportunities, critical information, innovations, advice, and ideas and can enable the exchange of knowledge and the creation of new knowledge, which may lead to enhanced opportunity recognition and ultimately to superior performance (McGrath & O’Toole, 2018; Randolph, Li, & Daspit, 2017).…”
Section: Analyzing Key Aspects Of the Dynamic Model For Successors’ Kmentioning
confidence: 99%
“…Prior studies show that the interaction between family and business does not necessarily create competitive advantage (Basco, 2013; O’Boyle et al, 2010); rather, it is critical to develop appropriate processes and capabilities (Basco, 2013; McGrath and O’Toole, 2018; Sirmon and Hitt, 2003). Drawing on the dynamic capability perspective (Eisenhardt and Martin, 2000; Teece et al, 1997), we explore the role of participative governance capability as an intermediary capability between internal social capital and international firm performance.…”
Section: Introductionmentioning
confidence: 99%